Effects of Foreign Ownership on Innovation Activities - Empirical Evidence for 12 European Countries - Martin Falk (FIW - Research Centre International Economics, 2008)
In the present study we investigate the relationship between foreign ownership and innovation activities using the firm-level data of the third Community Innovation Survey (CIS) covering 12 European countries. Probit estimates based on 28,000 firms observations show that foreign owned firms are more innovative than domestic firms, particularly in the New EU Member States. However, results from the Blinder Oaxaca decomposition of the differences in the percentage of innovating firms between foreign owned and domestic firms reveals that the differences are mainly due to the different firm characteristics rather than the differences in coefficients. In particular, the dominance of foreign owned firms in the largest firm size group is the main factor contributing to the gap in the percentage of innovators between foreign owned firms and domestic firms. Furthermore, using the fractional logit model, we find that in the New EU Member States, foreign ownership has a positive and significant impact on the share of market novelties as well as on the share of new products in turnover. In this case, the results from the Blinder Oaxaca decomposition analysis indicate that the ownership difference in the share of innovative sales is not due to the differences in the observed firms' characteristics.
Keywords: F23; C24; C25; L2; O3; 330; Foreign Direct Investment; foreign ownership; multinational firms; product and process innovations